Assessing Parental Stress and Satisfaction: Validation of the Hungarian Version of the Parental Stress Scale - Simon-Zámbori, Petra; Martos, Tamás; Sallay, Viola (European Journal of Mental Health, 2026)
Introduction: Parenting is widely recognized as a meaningful and rewarding experience, yet it also entails significant demands and stress. Major family transitions, beginning with the transition to parenthood and extending to later life changes, profoundly reshape family dynamics and are often associated with elevated parental stress. Therefore, reliable measures are essential to effectively capture the sources and effects of this stress. Aim: The current study aimed to examine parental stress in a Hungarian sample by validating the Parental Stress Scale (PASS; Berry & Jones, 1995). Methods: A cross-sectional study was conducted with 838 Hungarianspeaking parents (75.5% women; mean age = 37.50 years). Participants completed the Hungarian version of the Parental Stress Scale along with additional measures of perceived stress, depression, life satisfaction, parental resilience, and relationship satisfaction. Results: Exploratory factor analysis and confirmatory factor analysis with systematic model comparison supported a robust two-factor structure (Parental Stress and Parental Satisfaction) yielding a 13‑item solution with acceptable fit indices. Both scales demonstrated good internal consistency. Parental stress was positively associated with perceived stress and depression, and negatively associated with life satisfaction, parental resilience, and relationship satisfaction, whereas parental satisfaction showed the opposite pattern. Higher educational attainment and a greater number of children were associated with higher parental stress, while older age and male gender were associated with lower parental satisfaction. Conclusions: The Hungarian version of the Parental Stress Scale is a reliable and valid instrument for assessing parental stress and satisfaction. It serves as a useful tool for research and intervention programs aimed at supporting parental well-being in Hungary.